Licensing with Free Entry - Johannes Muthers; Firat Inceoglu; Toker Doganoglu (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The literature on the licensing of an innovation has mainly focused on some speci c contract types. We show within the framework of a fairly general model that removing these contractual limitations will lead to extreme market outcomes. Speci cally, we nd that when the patentee can employ observable contracts that can condition on market entry, it can achieve the monopoly outcome. Furthermore, when the patentee can only use unconditional quantity forcing contracts, it captures the entire market, albeit not at monopoly price, via a single licensee. Our results point out to the signi cance, and perhaps the particularity, of observable, nonrenegotiable contracts.
Keywords: D45; K11; L11; 330